2019
DOI: 10.1002/brb3.1467
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural changes in the visual pathway in multiple sclerosis

Abstract: IntroductionMultiple sclerosis (MS) is a heterogeneous disease with an unpredictable course. Visual pathway is a target of the disease and may reflect mechanisms that lead to disability. Structural and functional changes in the visual pathway may be studied by noninvasive techniques such as optical coherence tomography (OCT), visual evoked potentials (VEP), or B‐mode transorbital sonography (TOS).ObjectivesThe aim is to assess changes in the visual pathway in eyes of MS patients with and without a history of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 23 publications
1
18
2
Order By: Relevance
“…2,40 Our results agree with previous reports showing thinner pRFNL and FT in MS patients w/w ON history. 2,3,11 However, we did not find differences in the pRFNL between healthy and MS eyes without ON history (thinning lower than 2 μm), although it has been previously reported. 3,[40][41][42] The small difference between pRFNL of healthy versus MS patients without ON history is close to previously reported pRFNL repeatability achieved For personal use only.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…2,40 Our results agree with previous reports showing thinner pRFNL and FT in MS patients w/w ON history. 2,3,11 However, we did not find differences in the pRFNL between healthy and MS eyes without ON history (thinning lower than 2 μm), although it has been previously reported. 3,[40][41][42] The small difference between pRFNL of healthy versus MS patients without ON history is close to previously reported pRFNL repeatability achieved For personal use only.…”
Section: Discussioncontrasting
confidence: 69%
“…In fact, they obtain normal mean values of 86.8±21.4 µm to 104.7±12.5 µm while our values are lower even though our population of normal subjects is significantly younger (Table 1). The Cracelen-Gadea et al report 11 is of particular interest because it used the Spanish population of similar ages (35.0±5.84), with MS patients and because it is carried out with same equipment (Topcon SD 3D OCT). The pRNFL mean value in normal controls was 104.28±8.5 µm, in MS patients without ON it was 97.31±13.0 µm and in MS patients with past history of ON it was 93.5±11.8 µm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maria et al [ 36 ], reporting neuroradiologic data of a cohort of 46 JS patients, suggested an involvement of the myelination process in 33% of cases. This process is crucial for normal neural conduction along visual pathways, and it is well known that in demyelinating neurodegenerative diseases (i.e., multiple sclerosis), there is a delay in neural conduction along the visual pathways detectable by abnormal VEP responses (see Carcelén-Gadea et al for a review [ 37 ]). Thus, it is conceivable that also in JS patients there could be an abnormal myelination of nerve fibers forming the visual pathways, leading to the observed VEP abnormalities.…”
Section: Discussionmentioning
confidence: 99%